Trade-Off Regulation in Plant Growth and Stress Responses Through the Role of Heterotrimeric G Protein Signaling - Horim Lee (Plants)
Unlike animals, plants are sessile organisms that cannot migrate to more favorable conditions and must constantly adapt to a variety of biotic and abiotic stresses. Therefore, plants exhibit developmental plasticity to cope, which is probably based on the underlying trade-off mechanism that allocates energy expenditure between growth and stress responses to achieve appropriate growth and development under different environmental conditions. Plant heterotrimeric G protein signaling plays a crucial role in the trade-off involved in the regulation of normal growth and stress adaptation. This review examines the composition and signaling processes of heterotrimeric G proteins in plants, detailing how they balance growth and adaptive responses in plant immunity and thermomorphogenesis through recent advances in the field. Understanding the trade-offs associated with plant G protein signaling will have significant implications for agricultural innovation, particularly in the development of crops with improved resilience and minimal growth penalties under environmental stress.